2021
DOI: 10.21203/rs.3.rs-640156/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low-intensity, Long-wavelength Red Light Slows the Progression of Myopia in Children: an Eastern China-based Cohort

Abstract: Myopia is prevalent worldwide, particularly in East and Southeast Asia. Recent studies have suggested that the spectral composition of ambient lighting influences refractive development, especially in humans. We aimed to determine the effect of 650-nm single-wavelength red light on the inhibition of myopia progression in children. In this retrospective cohort study, 105 myopic children (spherical equivalent refractive error [SER], -6.75 to -1.00 dioptres (D)) aged from 4 to 14 years old were retrospectively re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…As shown in Table 5, those results were consistent with our previous report and the studies of Xiong et al 3,4,20 . It was shown that myopia among children could be controlled or reversed to some extent by PBM therapy, resulting in a mean decrease in the AL.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As shown in Table 5, those results were consistent with our previous report and the studies of Xiong et al 3,4,20 . It was shown that myopia among children could be controlled or reversed to some extent by PBM therapy, resulting in a mean decrease in the AL.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study found that the rate of AL change was approximately 0.25 mm/year (0.13 mm/year vs. 0.38 mm/year) slower in participants treated with repeated low-level red light than in controls 5 . The mean AL progression was 0.13 mm and 0.38 mm with a standard deviation (SD) of 0.15 mm after 1 year in the control group based on previous findings 3,4 . This was based on a two-sided statistical test with a 1% type I error threshold, 90% power and a 20% drop-out rate.…”
Section: Sample Size Calculationmentioning
confidence: 74%
See 1 more Smart Citation
“…Also, there have been multiple single-center clinical trials of other multifocal soft contact lenses in China, the United States, and Europe, but the variation in lens designs makes comparisons untenable. Likewise, emerging spectacle technologies 53,54 and low-level red-light therapy 55,56 have only been evaluated in Chinese children.…”
Section: Further Considerationsmentioning
confidence: 99%
“…A n increasing amount of attention has been devoted to interventions for myopia control in children, among which low-level red light (LLRL) [1][2][3][4][5][6] has recently attracted widespread interest. LLRL works by concentrating a specific band of light, typically 650 nm, into a laser beam to irradiate the retina.…”
mentioning
confidence: 99%